2014
DOI: 10.1111/cas.12477
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cancer recurrence in tumor margins by stopping microcirculation in the tumor and tumor–host interface

Abstract: Combretastatins interrupt blood flow of solid tumor vascular networks and lead to necrosis by blocking nutrients. However, tumors recover from tumor blood flow interruption-induced damage and develop viable rims. To investigate why cancer recurs and its prevention, we used a combretastatin derivative, Cderiv (=AC7700), and analyzed changes in tumor–host interface (T-HI) vessels, which were closest to cancer cells in the tumor margin after tumor vessel disruption, and the microenvironment surrounding them. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Numerous recent studies, for example by Kutsuyoshi et al . 28 , have analogously demonstrated that blocking both blood circulation routes (tumour and peri-tumourous vessels) has great potential as a clinical strategy to prevent cancer recurrence.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous recent studies, for example by Kutsuyoshi et al . 28 , have analogously demonstrated that blocking both blood circulation routes (tumour and peri-tumourous vessels) has great potential as a clinical strategy to prevent cancer recurrence.…”
Section: Discussionmentioning
confidence: 93%
“…The low extent of the antivascular effect might support the similar tumor viable rim area between mice treated with the Doxorubicin formulations and non-treated mice (Figure 3.6B). Additionally, nontumoral vessels from surrounding tissues are also expected to provide nutrient and oxygen supplies to cells in the peritumoral region 451,452 . Altogether, these factors likely contributed to the maintenance of viable areas in the tumor mass that fuels its expansion and invasion (Figure 3.6A), and could be responsible for the tumor regrowth observed in some Caelyx®treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…The low extent of the antivascular effect might support the similar tumor viable rim area between mice treated with Caelyx® and non-treated mice (Fig 4D). Additionally, non-tumoral vessels from surrounding tissues are also expected to provide nutrient and oxygen supplies to cancer cells [71, 72]. These factors likely contributed to the maintenance of tumor viable areas that fuels its expansion and invasion (Fig 4C), and could be responsible for the tumor regrowth observed in some Caelyx®-treated mice.…”
Section: Discussionmentioning
confidence: 99%